Case Report: CTC1 mutations in a patient with diffuse hepatic and splenic hemangiomatosis complicated by Kasabach–Merritt syndrome - He, Xin; Guo, Zi-Wen; Niu, Xiao-Min (Frontiers in Oncology, 2023)
Diffuse hemangiomatosis of the liver and spleen is rare. Currently, few studies are available on diffuse hepatic and splenic hemangiomatosis accompanied with Kasabach–Merritt syndrome(KMS). The conserved telomere maintenance component 1 (CTC1) gene contributes to telomere maintenance and replication by forming the telomeric capping complex. Herein, we report a case of diffuse hemangiomatosis in the liver and spleen accompanied with KMS in a 59-year-old woman who carried two novel heterozygous CTC1 variants: c.435+9A>C and c.3074C>T, p.Ala1025Val. Using next-generation sequencing, we detected mutations in the CTC1 gene in our patient who had chief complaints of fatigue and abdominal distension complicated by severe thrombocytopenia and consumptive coagulopathy. Clinical symptoms, laboratory tests, and imaging findings led to the diagnosis of diffuse hepatic and splenic hemangiomatosis accompanied with KMS. The patient was treated with prednisone, thalidomide, and sirolimus, and her general condition was ameliorated at the 4-month follow-up, with improved platelet count and coagulation function. A CTC1 gene mutation may be involved in the pathological process of vascular diseases. A combination treatment regimen of prednisone, thalidomide, and sirolimus may be effective for KMS.